Helicopter aft-body drag reduction by passive flow control - Grawunder, M.; Ress, R.; Breitsamter, C. (My University, 2014)
The reduction of emissions in air transport is clearly a main goal of the aeronautical industry today, addressing both fixed wing aircraft and rotorcraft. The ADHeRo (Aerodynamic Design Optimization of a Helicopter Fuselage including a Rotating Rotor Head) project contributed to achieving this goal by providing detailed flow characteristics and drag analysis of a state-of-the-art Twin Engine Light (TEL) class utility helicopter with passive flow control devices. This was achieved by means of wind tunnel experiments and numerical simulations. It has been shown that optimizing the aerodynamic design of the skid-landing-gear is a vital approach for achieving efficiency gains in the twin-engine-light helicopter class. However, further drag reduction potential was identified for the rear fuselage upsweep region. Even though the aerodynamic interference of the modified skid-landing-gear with the fuselage is reduced, it is not entirely eliminated. Thus, the remaining separation at the rear fuselage upsweep provides additional drag reduction potential. Furthermore, the strong lateral tapering of the rear fuselage region also causes the flow to separate from the either side of the fuselage. Delaying this lateral separation also provides drag reduction potential. Design constraints for the requested rear loading capability do not allow streamlining the aft-body region, i.e. implementing a ‘fish-tail’ configuration. Thus, the current work is addressing these drag sources through the application of passive flow control devices. The selected devices (strakes and vortex generators) are applied to the rear fuselage upsweep region. In this study counter-rotating vortex generators, simple sheet-metal type strakes and contoured strakes are investigated. This includes a wide experimental analysis of the devices optimal position and their combination. Compared to current production type TEL utility helicopter, the parasite drag could be reduced by another 1.4 - 1.6% in addition to the previous drag savings obtained with the faired skid-landing-gear (21 %).